Impact of social and labour plans in alleviating poverty in Matjhabeng Municipality - Mathabela, Matsidiso Selina (My University, 2011)
The aim of this study is to assess the impact of Social and Labour Plan interventions on the socioeconomic wellbeing of ex-miners and their communities in Matjhabeng, a local municipality in the Free State. In pursuit of this objective, data were gathered from key stakeholder groups such as exmineworkers, union officials, mine officials and the local municipality. Exmineworkers participated in a survey and focus group discussions and the other stakeholders participated in dyadic interviews. The findings indicate that stakeholders do not share the same understanding of the objectives, strategies and processes of the Social and Labour Plan. Interventions were fragmented and marred by silos and there is a noticeable lack of integrated planning. Solutions that underpin a return to the fundamentals of organisational and project management are recommended
MM - P&DM
Keywords: Poverty alleviation; Local authorities